2010
DOI: 10.1136/qshc.2008.030700
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture: factors that influence clinician involvement in patient safety behaviours

Abstract: Professional peer-modelling behaviours and individuals' beliefs about the value of those behaviours in improving patient safety are important predictors of HCWs' patient safety behaviour. These findings may help explain the limitations of current knowledge-based educational approaches to patient safety reform. Use of the behavioural models developed in this study when designing future patient safety improvement initiatives may prove more effective in driving the behavioural change necessary for improved patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 44 publications
(28 reference statements)
2
91
0
2
Order By: Relevance
“…Als entscheidend für die Etablierung einer Sicherheitskultur und für die Umsetzung sicherer Handlungsweisen für Patienten wird die Vorbildfunktion erfahrener Ärzte gesehen[9,10].Bedingung der Bereitschaft, patientensichere Handlungen vorzunehmen, ist die Kenntnis solcher Handlungsweisen. Es konnte gezeigt werden, dass die Ausbildung neuer Ärztegenerationen in empfohlenen sicheren Methoden bspw.…”
unclassified
“…Als entscheidend für die Etablierung einer Sicherheitskultur und für die Umsetzung sicherer Handlungsweisen für Patienten wird die Vorbildfunktion erfahrener Ärzte gesehen[9,10].Bedingung der Bereitschaft, patientensichere Handlungen vorzunehmen, ist die Kenntnis solcher Handlungsweisen. Es konnte gezeigt werden, dass die Ausbildung neuer Ärztegenerationen in empfohlenen sicheren Methoden bspw.…”
unclassified
“…63 As a subset of organisational culture, safety culture comprises these attributes as they relate to patient safety. Facets of a positive safety culture include: ■ norms and rules for handling hazards, attitudes towards safety; reflexivity on safety practice 64 ■ positive attitudes to safety behaviours and role modelling of such behaviours to peers and juniors 65 ■ recognition of the inevitability of error and proactively seeking to identify latent threats 55,66 ■ non-punitive reporting systems, analysis of errors and near-misses, feedback to frontline staff, sharing learning 3,57,67 ■ openness, fairness and accountability at all organisational levels 68 ■ well-functioning teams 11,12,55,[69][70][71][72][73] ■ maintenance of situational awareness among team members 34,74,75 ■ non-hierarchical teams in which roles are flexible 76,77 and staff at all levels feel empowered 78 and ■ attention to staff development, 67,79 with consequent reduction in staff stress and burnout. 80,81 Wide variation in the framing of organisational and safety cultures and climates makes it inevitable that there will be little agreement on how they should be observed or measured.…”
Section: Organisational and Safety Cultures: Concepts And Definitionsmentioning
confidence: 99%
“…communication openness, routine feedback, non-punitive culture) has a large influence on reporting by health practitioners. 165,166,173 Australian research found that the observed behaviour of professional peers and a belief that safety behaviours will make a difference, were the two factors most influential on the safety behaviours of health care workers. No reactions were reported to the TGA during the study period, including two reported reactions of extrapyramidal side effects from metoclopramide at standard doses and one case of extrapyramidal effects attributed to ondansetron.…”
Section: Discussionmentioning
confidence: 99%
“…These results correspond closely to the findings listed above with incident reporting and other health practitioners. 166 Despite these barriers, and the limitations of pharmacist intervention reporting, the combination of incident reports with health practitioner interventions into a single reporting system is considered a valuable method to identify faulty processes.…”
Section: Interventions (Pharmacist or Nursing)mentioning
confidence: 99%
See 1 more Smart Citation